P017: A time-driven activity-based costing method to estimate health care costs in the emergency department. (15th May 2017) - Berthelot, S.; Mallet, M.; Baril, L.; Dupont, P.; Bissonnette, L.; Stelfox, H.; Émond, M.; Blais, S.; Vezo, A.; Létourneau, M.; Côté, S.; Bécotte, G.; et al.
Abstract : Introduction: Poor physicians' knowledge of health care costs has been identified as an important barrier to improving efficiency and reducing overuse in care delivery. Moreover, costs of tests and treatments estimated with traditional costing methods have been shown to be imprecise and unreliable. We estimated the cost of frequent care activities in the emergency department (ED) using the time-driven activity-based costing (TDABC) method.Methods: We conducted a TDABC study in the ED of the CHUL, Québec city (77000 visits/year). We estimated the cost of all potential care activities (e.g. triage) provided to adult patients with selected urgent (e.g. pulmonary sepsis) and non urgent (e.g. urinary tract infection) conditions frequently encountered in the ED. Following Lean management principles, process maps were developed by a group of ED care providers for each care activity to identify human resources, supplies and equipment involved, and to estimate the time required to complete each process. Resource unit cost (e.g. cost per minute of a nurse) and overhead rate were calculated using financial information from fiscal year 2015-16. Estimated cost of each care activity (e.g. chest X-ray) including physicians' charges was calculated by summing overhead allocation and the cost of each process (e.g. disinfection of the X-ray machine) as obtained by multiplying the resource unit cost by the time for process completion.Results: Process maps were developed for 14 conditions and 68 ED care activities. We estimated the costs of activities (CAN$) related to nursing (e.g. urinalysis and culture triage ordering $14.70), clerk tasks (e.g. patient registration $3.40), physicians (e.g. FAST scan $20.90), laboratory testing (e.g. CBC $6.30), diagnostic imaging (e.g. abdominal CT scan $146.50), therapy (e.g. 5 mg of iv morphine $20.40), and resuscitation (rapid sequence intubation with ketamine and succinylcholine $146.40). Overall, emergency physicians' charges, personnel salaries and overheads accounted for 38%, 22% and 16% of all ED care costs, respectively.Conclusion: Our results represent an important step toward increasing emergency physicians' awareness on the real cost of their interventions and empowering them to adopt more cost-effective practice patterns.